2021
DOI: 10.14283/jpad.2021.20
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Recruitment Source and Participant Communication Preferences for Alzheimer’s Disease Prevention Research

Abstract: Background: Evidence on effective engagement of diverse participants in AD prevention research is lacking. Objectives: To quantify recruitment source in relation to race, ethnicity, and retention. Design: Prospective cohort study. Setting: University lab. Participants: Participants included older adults (N=1170) who identified as White (86%), Black (8%), and Hispanic/Latino ethnicity (6%). Measurements: The Cognitive Aging Lab Marketing Questionnaire assessed recruitment source, social media use, and researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous research in AD recruitment has indicated preferences among certain minority groups for newspaper recruitment, community referrals, or text messaging. 10 , 11 Additionally, certain community outreach programs have been shown to be more effective methods of recruiting these diverse populations compared to this study's experience. 10 , 11 …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous research in AD recruitment has indicated preferences among certain minority groups for newspaper recruitment, community referrals, or text messaging. 10 , 11 Additionally, certain community outreach programs have been shown to be more effective methods of recruiting these diverse populations compared to this study's experience. 10 , 11 …”
Section: Discussionmentioning
confidence: 75%
“… 10 , 11 Additionally, certain community outreach programs have been shown to be more effective methods of recruiting these diverse populations compared to this study's experience. 10 , 11 …”
Section: Discussionmentioning
confidence: 75%